Epidemic and VP1 genetic characteristics of coxsackievirus A8 in Guangdong province, 2010 - 2020 - Xiao-li CHEN; Han-ri ZENG; Huan-ying ZHENG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo study the epidemic and genetic characteristics of coxsackievirus A8 (CVA8) in Guangdong province. MethodsFrom all specimens sampled in hand, foot, and mouth disease (HFMD) cases reported during 2010 - 2020 in Guangdong province, we collected those of other enterovirus (EV) - non-EV71/CVA16/CVA6. After amplified VP1 gene based-genotype identification, CVA8 strains were isolated from the specimens using rhabdomyosarcoma (RDa) cells. The entire VP1 region of the isolated CVA8 strains were amplified and sequenced and then phylogenetically analyzed using DNASTAR6.0 and MEGA6.06 software packages. ResultsOf totally 2650 other EV specimens collected during the period, 2.6% (69) were positive for CVA8 and the annual ratio of CVA8 positive specimens ranged from 0.5% to 12.0%, with the highest ratio in 2020. The CVA8 positive specimens were detected in 13 cities of the province and the highest clustering of positive specimens (28) was detected in Shantou city during July - November 2020. CVA8 strains were isolated from 73.9% (51) of the positive specimens. The phylogenetic analysis results indicated that CVA8 could be divided into five genotypes: A, B, C, D and E. The 44 CVA8 strains isolated in this study shared 77.8% - 100.0% homologies in nucleotide and 92.9% - 100.0% in amino acid, including genotype D (5 strains) and genotype E (39 strains), and the nucleotide homology of 28 CVA8 strains isolated in Shantou city during July - November 2020 was 99.3% - 100.0%. ConclusionCVA8 was prevalent sporadically in Guangdong province during 2010 - 2020 generally but highly prevalence among local HFMD cases in Shantou city during July - November 2020. CVA8 strains of genotype D and E were prevalent and strains of genotype E are currently prevalent in Guangdong province.